Ukraine : Trade Policy Study, Volume 1. Main Conclusions and Recommendations - World Bank (Washington, DC, 2013)
The main objectives of this study are the following: 1) foster a better understanding of key drivers of recent trade performance; 2) assess current trade policies and provide additional recommendations to strengthen the Government's trade integration strategy; 3) identify core bottlenecks in the ongoing integration processes, especially with WTO accession; and 4) develop recommendations for Ukraine's international partners to provide Ukraine with a level playing field in terms in international trade, and the government with additional technical assistance that would help Ukraine upgrade its trade policies and institutions. The report's main messages are: The current trade patterns are unsustainable in the longer term because they depend heavily on temporary factors. Significant export diversification is critical for export to become a reliable source of future economic growth. The main obstacles to furthering Ukraine's trade integration are domestic and relate to serious deficiencies in the business environment, specifically in customs administration, standardization, and administrative barriers for new entry require immediate attention. To utilize its potential, it needs to drastically increase inward foreign direct investment (FDI). The policy of global trade integration should be given priority over regional integration processes. Completing WTO accession is an over-riding policy priority for Ukraine. A simultaneous push toward free trade arrangements in both directions (EU and CIS) fits well with Ukraine's longer-term interests. Efforts to advance free trade should be de-linked from other policy objectives (such as EU membership and CIS Customs Union).